A review on the alternative of indium tin oxide coated glass substrate in flexible and bendable organic optoelectronic device. (14th July 2022) - Shankar, Uday; Oberoi, Deepa; Bandyopadhyay, Anasuya
Abstract: Flexible and optically transparent electrodes (TEs) are essential for most state‐of‐art organic optoelectronic devices (OOED). The demand for bendable electronic devices with aesthetic impact and multi‐functionality has driven the rapid development of flexible TEs with improved optoelectrical and mechanical properties. However, conventional rigid TEs, that is, indium tin oxide (ITO) coated glass substrate (ITO/glass), cannot match smart devices' requirements in unique fields, like electrochromic devices, electronic skins, and wearable electronics, foldable displays, smart windows, and solar cells. To substitute extensively used ITO/glass electrodes has been endeavored because of the increasing price and inherently brittle ITO and glass substrate behavior. Emerging TEs based on the combination of the polymers substrate and conducting fillers like graphene, carbon nanotubes, metal nanowires, and transparent conducting oxides are bendable, lightweight, and inexpensive. They have shown substantial prospects to be used in the devices mentioned above. With each tiny development in these emerging TE's, such as outstanding optoelectrical and mechanical features in flexible electrodes, they become more suitable for practical applications in miscellaneous bendable devices. This review summarizes the comprehensive overview of the modern alternative flexible TEs and their implementation in bendable and stretchable devices.